Acranthera burmanica, a new species of Rubiaceae from Kachin State, Myanmar - Tan, Yun-Hong; Yang, Bin; Li, Jian-Wu; Zhou, Shi-Shun; Shwelone, Shwelone; Khaing, Kyikyi; Li, Ren; Huang, Jian-Ping; Sun, Hang (Phytotaxa, 2015)
Acranthera burmanica, a new species of Rubiaceae from Kachin, Myanmar, is here described and illustrated. It is morphologically similar to A. sinensis, but can be easily distinguished from the latter by its stem and branches densely strigose throughout; ovate leaves; calyx distinctly shorter than corolla tube, lobes lanceolate, apex attenuate; stipules triangular, apex acute not cuspidate; lower part of filaments connate into a tube.